Repurposing FDA-approved drugs as therapeutics to treat Rift Valley fever virus infection - Benedict, Ashwini; Bansal, Neha; Senina, Svetlana; Hooper, Idris; Lundberg, Lindsay; de la Fuente, Cynthia; Narayanan, Aarthi; Gutting, Bradford; Kehn-Hall, Kylene (Frontiers in Microbiology, 2015)
There are currently no FDA-approved therapeutics available to treat Rift Valley fever virus (RVFV) infection. In an effort to repurpose drugs for RVFV treatment, a library of FDA-approved drugs was screened to determine their ability to inhibit RVFV. Several drugs from varying compound classes, including inhibitors of growth factor receptors, microtubule assembly/disassembly, and DNA synthesis, were found to reduce RVFV replication. The hepatocellular and renal cell carcinoma drug, sorafenib, was the most effective inhibitor, being non-toxic and demonstrating inhibition of RVFV in a cell-type and virus strain independent manner. Mechanism of action studies indicated that sorafenib targets at least two stages in the virus infectious cycle, RNA synthesis and viral egress. Computational modeling studies also support this conclusion. siRNA knockdown of Raf proteins indicated that non-classical targets of sorafenib are likely important for the replication of RVFV.